The impact of media and social media on residents' perception of the frequency of crime occurences in Shah Alam: a multinomial logistic regression approach / Noor Syafiqah Ariffin, Nur Hanim Aziz and Nur Fadhilah Anis Mansor - Ariffin, Noor Syafiqah; Aziz, Nur Hanim; Mansor, Nur Fadhilah Anis (2019)
This research was to determine the impact of media and social media on residents' perceptions of crime occurrences in Shah Alam. In addition, the researcher was interested to determine the extent to which perception of crime occurrences were related to the mass media. The information required for the study was obtained through a self¬ administered questionnaire distributed in public areas including shopping mall, mosque, food court, library and University in Shah Alam. By using convenience sampling method, 300 Shah Alam residents were selected as respondents. A Multinomial Logistic Regression analysis shows social media and media influenced their perceptions of how frequently crime occurs in Shah Alam. More specifically, social media had a greater influence on the resident's perception of crime occurrences in Shah Alam than media. In addition, gender, race and view social media posts on crime were significantly to the Shah Alam residents' perceptions of crime occurrences. The findings from this study provide insights to the citizens with information related to crime and how technology could be an element of interest and influence.